PERAMALAN KEBUTUHAN PERSEDIAAN OBAT PADA UPT. PUSKESMAS TANJUNG HABULU - Assiva, Isri; Noor Hayatie, Marliza; Hirdianti Bandi, Maulida; Suasri, Eni (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2025)
The Tanjung Habulu Community Health Center (UPT Puskesmas Tanjung Habulu), located in Tanjung village, Bajuin District, faces challenges in drug supply, having experienced shortages in the past. Therefore, a study was conducted comparing the weighted moving average method and the single exponential smoothing method to forecast the inventory of Amlodipine 10 mg, Glimipiride 2 mg, and Piroxicam 10 mg capsules for the upcoming period. To assess the accuracy of these methods in forecasting drug inventory on a quarterly basis, the Mean Absolute Percentage Error (MAPE) was utilized. Based on the research findings, it can be concluded that the weighted moving average method outperforms the single exponential smoothing method due to its smaller MAPE value. Forecasting results using the Weighted Moving Average method are Amlodipine 10 mg totaling 9,898 tablets and a MAPE value of 10%, Glimpiride 2 mg totaling 4,650 tablets and a MAPE value of 15%, and Piroxicam capsules 10 mg totaling 3,460 tablets and a MAPE value of 9%.